2017
DOI: 10.1200/jco.2017.35.15_suppl.9084
|View full text |Cite
|
Sign up to set email alerts
|

Response to salvage chemotherapy following exposure to immune checkpoint inhibitors in patients with non-small cell lung cancer.

Abstract: 9084 Background: Immune checkpoint inhibitors are active for patients with stage IV NSCLC who have progressed following platinum-based chemotherapy. We evaluated responses to chemotherapy in patients who had progressed on a checkpoint inhibitor. Methods: Eligible patients were adults with NSCLC who received salvage chemotherapy following PD-1/PD-L1 inhibitors (cases) versus no PD-1/PD-L1 inhibitors (controls). CT-imaging was done within 4 weeks of initiation of salvage chemotherapy and every 6 weeks thereafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 0 publications
7
40
0
1
Order By: Relevance
“…Third‐line cytotoxic chemotherapy has been reported to have a low response rate of 3–9% . Recently, three retrospective studies, including a case–control study, presented a promising response rate of 25–39% after salvage chemotherapy following exposure to PD‐1/PD‐L1 inhibitors (Table ) . The case–control study revealed an odds ratio of 0.30 (95% confidence interval 0.18–0.50) for achieving a partial response to salvage chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third‐line cytotoxic chemotherapy has been reported to have a low response rate of 3–9% . Recently, three retrospective studies, including a case–control study, presented a promising response rate of 25–39% after salvage chemotherapy following exposure to PD‐1/PD‐L1 inhibitors (Table ) . The case–control study revealed an odds ratio of 0.30 (95% confidence interval 0.18–0.50) for achieving a partial response to salvage chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three retrospective studies, including a case–control study, presented a promising response rate of 25–39% after salvage chemotherapy following exposure to PD‐1/PD‐L1 inhibitors (Table ) . The case–control study revealed an odds ratio of 0.30 (95% confidence interval 0.18–0.50) for achieving a partial response to salvage chemotherapy . In phase I/II trials, concurrent administration of the PD‐1 inhibitor with first‐line chemotherapy showed a high response rate of > 50% .…”
Section: Discussionmentioning
confidence: 99%
“…We have reported the drastic regression of lung cancer cases treated with chemotherapy following nivolumab, which is known as salvage chemotherapy . Several recent studies have also shown that the combination therapy of PD‐1 inhibitors with anti‐cancer drugs, including salvage chemotherapy, produces high anti‐tumor activity in some patients . Salvage chemotherapy showed a high objective response rate of 38% (95% confidence interval [CI] 31.3–44.7%) in a total of 200 cases obtained from four retrospective studies …”
Section: Introductionmentioning
confidence: 99%
“…In support of this, patients with NSCLC who were randomized to front‐line pembrolizumab followed by investigator‐choice cytotoxic therapy, which was paclitaxel in 19% of patients, had a longer time to progression after the initiation of second‐line therapy compared with patients randomized to front‐line cytotoxic therapy followed by investigator‐choice therapy, which usually consisted of PD‐1 blockade (KEYNOTE‐024) . A similar pattern was observed in a separate NSCLC study, which showed that salvage chemotherapy was associated with a response rate of 27% among patients with prior exposure to PD‐1/PD‐L1 inhibitors versus 7% without prior exposure .…”
Section: Discussionmentioning
confidence: 65%
“…Recent data from non‐small cell lung cancer (NSCLC) suggest that anti‐PD‐1 therapy may enhance sensitivity to subsequent chemotherapy . To date, reports on treatment efficacy after failure of PD‐1 blockade in advanced gastroesophageal adenocarcinoma are lacking.…”
Section: Introductionmentioning
confidence: 99%